Metode Partial Least Square (PLS) untuk Menganalisis Kepuasan Pengunjung Terhadap Pelayanan Kantor Camat Koto Tangah Kota Padang - Nadia Liaf Putri; Dewi Murni (UNIVERSITAS NEGERI PADANG, 2021)
Partial Least Square (PLS) method is methods used to analyze visitor satisfaction. Analysis of visitor satisfaction is useful for an agency in an effort to improve the quality of services provided. The purpose of this study was to determine the form of the PLS model in analyzing visitor satisfaction with the services of the Koto Tangah sub-district office and to determine the effect of service quality on visitor satisfaction. The variable used is the visitor satisfaction variable is namely tangibles, reliability, responsiveness, assurance, and empathy. The steps of data analysis carried out were designing a structural relationship model, making measurement models, evaluating structural models and testing hypotheses. Based on the analysis that has been done, it shows that the service quality variable has a positive and significant influence on visitor satisfaction. In the PLS method, the structural equation is obtained, Satisfaction = 0.087 Tangibles + 0.103 Reliability + 0.371 Responsivess + 0.052 Assurance + 0.445 Empathy + ε.